2013
DOI: 10.3389/fpsyg.2013.00653
|View full text |Cite
|
Sign up to set email alerts
|

Can mergers-in-progress be unmerged in speech accommodation?

Abstract: This study examines spontaneous phonetic accommodation of a dialect with distinct categories by speakers who are in the process of merging those categories. We focus on the merger of the NEAR and SQUARE lexical sets in New Zealand English, presenting New Zealand participants with an unmerged speaker of Australian English. Mergers-in-progress are a uniquely interesting sound change as they showcase the asymmetry between speech perception and production. Yet, we examine mergers using spontaneous phonetic imitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…As in Pardo, Jordan, et al (2013), the present study reveals that talkers do not imitate all acoustic-phonetic attributes in the same manner (see also Babel & Bulatov, 2012;Babel et al, 2013;Levitan & Hirschberg, 2011;Pardo et al, 2010;Pardo Gibbons, Suppes, & Krauss, 2012;Pardo, Cajori Jay, et al, 2013;Walker & Campbell-Kibler, 2015). No single attribute drives convergence, and talkers converge on some attributes at the same time that they diverge or fail to converge on others.…”
Section: Attributes and Measures Of Phonetic Convergencementioning
confidence: 48%
See 2 more Smart Citations
“…As in Pardo, Jordan, et al (2013), the present study reveals that talkers do not imitate all acoustic-phonetic attributes in the same manner (see also Babel & Bulatov, 2012;Babel et al, 2013;Levitan & Hirschberg, 2011;Pardo et al, 2010;Pardo Gibbons, Suppes, & Krauss, 2012;Pardo, Cajori Jay, et al, 2013;Walker & Campbell-Kibler, 2015). No single attribute drives convergence, and talkers converge on some attributes at the same time that they diverge or fail to converge on others.…”
Section: Attributes and Measures Of Phonetic Convergencementioning
confidence: 48%
“…As summarized earlier, many explanations of phonetic convergence focus on its role in promoting social interaction by reducing social distance or increasing liking of a conversational partner. Although it is often useful to examine convergence in an individual acoustic parameter when assessing questions related to specific accents or attributes of sound change (e.g., Babel, 2010;Babel, McAuliffe, & Haber, 2013;Delvaux & Soquet, 2007;Dufour & Nguyen, 2013;Mitterer & Ernestus, 2008;Mitterer & Müsseler, 2013;Olmstead, Viswanathan, Aivar, & Manuel, 2013;Nguyen, Dufour, & Brunellière, 2012;Walker & Campbell-Kibler, 2015), assessments of a single acoustic attribute are limited with respect to broader interpretations of the phenomenon. For example, studies of convergence in VOT have often reported small changes toward a model's extended VOT values (usually around 10 ms or less; Fowler et al, 2003;Nielsen, 2011;Shockley, Sabadini, & Fowler, 2004;Yu, Abrego-Collier, & Sonderegger, 2013).…”
Section: Effects Of Word Frequency and Talker Sexmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Andalusian Spanish, the question is whether a speaker who realizes the contrast between /t/ and /st/ in production based on post-aspiration is also more sensitive to post-aspiration as a cue to the /t/-/st/ distinction in perception. However, empirical work on vowel mergers illustrates how perception and production can be misaligned, that is, how a perceived phonological contrast is by the same speaker merged in production (Babel et al, 2013;Labov et al, 1991). Further evidence against a direct production-perception link comes from studies on compensation for coarticulation (Grosvald & Corina, 2012;Kataoka, 2011) in which the degree between perceptual compensation for coarticulation and the production of coarticulation was not correlated within speakers.…”
Section: Sound Change Actuationmentioning
confidence: 99%
“…Speech accommodation refers to a situation in which the speech patterns of interacting speakers become more similar, or converge, over the course of a conversation. In part because accommodation has been argued to be a vehicle for dialect acquisition and sound change ( [1], [2], [3]), it has received extensive investigation in recent years at various linguistic levels, including syntactic structure ( [4], [5], [6]), lexical items ( [7], [8], [9]), and phonetic features ( [10], [11]). The goal of this study is to investigate accommodation at the prosodic level, specifically prosodic boundaries, in order to gain a better understanding of the ways in which prosodic properties might be similarly malleable.…”
Section: Introductionmentioning
confidence: 99%